Edukasi Mencegah Penyakit Demam Berdarah Dengue (DBD) pada Masyarakat di Kelurahan Tahtul Yaman - Willia Novita Eka Rini; Marta Butar Butar; Budi Aswin; Evy Wisudariani; La Ode Reskiaddin; Yeni Marlina; Mutiara Salsabila; Muhammad Gusman Syahlun Abyan (Lembaga Pengembangan Kinerja Dosen, 2024)
Dengue fever is still one of the main health problems that threaten people in Indonesia, including Jambi City. Tahtul Yaman neighbourhood, Jambi Province is one of the residential areas that has dengue fever data. In general, most residents use water tanks, the environment looks less clean, and there are still puddles and water reservoirs in the homes of some residents. This activity aims to provide knowledge and understanding to the community about dengue fever and its mitigation strategies, with an emphasis on prevention through vector control, especially the Aedes aegypti mosquito. This counselling will be focused on the Tahtul Yaman Village community. The method used was lecture method and interactive discussion using powerpoint, posters and leaflets on DHF and 3M Plus. After the education, there was an increase in knowledge reaching 89.25%. It is suggested that prevention efforts should focus on controlling the larval population and minimising mosquito breeding sites. Mosquito eradication programmes such as 3M Plus need to be carried out routinely and involve the active participation of the entire community. Effective dengue prevention will create a healthier and safer environment for the community.